2004
DOI: 10.1007/s00441-004-0966-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase expression in cultured growth plate chondrocytes during differentiation

Abstract: Hyaluronan (HA) is a major component of the extracellular matrix of cartilage, contributes to its structural and functional integrity, and has various important roles in the differentiation of chondrocytes. HA metabolism is regulated by both anabolic and catabolic processes; however, the details have not yet been clarified. The purpose of this study was to clarify the expression patterns of hyaluronidase (HAase) mRNAs (from the relevant HAase genes: the HYALs) and HAase activity during chondrocyte differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Other studies show that HA released from rabbit growth plate chondrocytes during in vitro differentiation has a broad ranging 404 E. R. Bastow et al Synthesis and degradation of hyaluronan molecular mass [226]. Since hyal1 and hyal2 are expressed in the proliferative and hypertrophic zones of rabbit growth plate [227], these results suggest that HYALs, and synthases producing high M r HA, are active concurrently. Depolymerisation of HA by HYALs in growth plate cartilage will simultaneously depolymerise the HAaggrecan-link protein aggregates.…”
Section: Hyals and Hass In Longitudinal Bone Growthmentioning
confidence: 80%
“…Other studies show that HA released from rabbit growth plate chondrocytes during in vitro differentiation has a broad ranging 404 E. R. Bastow et al Synthesis and degradation of hyaluronan molecular mass [226]. Since hyal1 and hyal2 are expressed in the proliferative and hypertrophic zones of rabbit growth plate [227], these results suggest that HYALs, and synthases producing high M r HA, are active concurrently. Depolymerisation of HA by HYALs in growth plate cartilage will simultaneously depolymerise the HAaggrecan-link protein aggregates.…”
Section: Hyals and Hass In Longitudinal Bone Growthmentioning
confidence: 80%
“…Furthermore, future studies would ideally investigate NP and AF cells separately, although our own preliminary data on bovine NP and AF cells indicate marginal zonal differences in HYAL expression. Increased HYAL expression and/or activity have been described in numerous pathologies, such as during asthma (within the epithelium) [30], cartilage hypertrophy [52] or osteoarthritis and rheumatoid arthritis (within the knee synovium/synoviocytes) [53,54]. HYAL deficiency or knockdown/knockout have also been described to promote certain pathologies, leading, e.g., to swelling of the periarticular masses [55] as well as to progression of osteoarthritis [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…HYAL3 which belongs to the Hyaluronan family, the major component of the extracellular matrix of cartilage, contributes to its structural and functional integrity. Tanimoto et al demonstrated that the selective expression of HYALs is essential for extracellular HA metabolism during chondrocyte differentiation 20…”
Section: Discussionmentioning
confidence: 99%
“…Tanimoto et al demonstrated that the selective expression of HYALs is essential for extracellular HA metabolism during chondrocyte differentiation. 20 Other genes related to the immune system are modulated. This mechanism could be related to the osseointegration process: indeed the inserted material has to be recognized as ''self'' by the immune system.…”
Section: Discussionmentioning
confidence: 99%